The differential response to neuronal hyperexcitation and neuroinflammation of the hippocampal neurogenic niche - Ruiz-Clavijo, Lorena; Martín-Suárez, Soraya (Frontiers in Neuroscience, 2023)
Hippocampal neurogenesis is a tightly regulated process in which neural stem cells (NSCs) get activated, enter in the cell cycle and give rise to neurons after a multistep process. Quiescent and activated NSCs, neural precursors, immature and mature neurons and newborn astrocytes coexist in the neurogenic niche in a strictly controlled environment which maintains the correct functioning of neurogenesis. NSCs are the first step in the neurogenic process and are a finite and, mostly, non-renewable resource, therefore any alteration of the intrinsic properties of NSCs will impact the total neurogenic output. Neuronal hyperexcitation is a strong activator of NSCs prompting them to divide and therefore increasing neurogenesis. However, neuronal hyperactivity is not an isolated process but often also involves excitotoxicity which is subsequently accompanied by neuroinflammation. Neuroinflammation normally reduces the activation of NSCs. It is technically difficult to isolate the effect of neuronal hyperexcitation alone, but neuroinflammation without neuronal hyperexcitation can be studied in a variety of models. In order to shed light on how the balance of neuronal hyperexcitation and neuroinflammation affect NSCs we analyzed proliferation and morphology of NSCs. We used two models of neuronal hyperactivity (an epilepsy model induced by KA, and a model of traumatic brain injury (TBI)) and different models of inflammation (LPS,Poly I:C, IFN-α and IL-6). We observed that only those models that induce neuronal hyperactivity induce NSCs activation but neuroinflammation causes the opposite effect. We also analyzed the response of other cell types in the neurogenic niche, focusing on astrocytes.